2012
DOI: 10.1007/978-3-642-31131-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Safety Slicing Petri Nets

Abstract: Abstract. We define a safety slice as a subnet of a marked Petri net Σ that approximates Σ's temporal behavior with respect to a set of interesting places Crit. This safety slice can be used to verify and falsify stutter-invariant linear-time safety properties when Crit is the set of places referred to by the safety property. By construction it is guaranteed that the safety slice's state space is at most as big as that of the original net. Results on a benchmark set demonstrate effective reductions on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In this section, we will study basic algorithms for static PN slicing [2][3][4][5][7][8][9]. The objective of every algorithm is to improve the verification process either by reducing a PN model or by partitioning a PN model.…”
Section: Static Slicing Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we will study basic algorithms for static PN slicing [2][3][4][5][7][8][9]. The objective of every algorithm is to improve the verification process either by reducing a PN model or by partitioning a PN model.…”
Section: Static Slicing Algorithmsmentioning
confidence: 99%
“…In this article, we review existing PN slicing techniques that can be found in the present iterature [2][3][4][5][6][7][8][9]12]. We have two objectives, the first is to unify all the existing slicing algorithms syntactically and the second is to discuss the contribution of each work and compare major semantic differences between them.…”
Section: Introductionmentioning
confidence: 99%
“…The conception of reading and nonreading transitions is introduced in [18] for the first time. Informally, reading transitions are not supposed to change the marking of a place.…”
Section: Unfolding Slicing and Verifying Apnsmentioning
confidence: 99%
“…The reduced model contains only those parts that may affect the property the model is analyzed for. Slicing Petri nets is gaining much attention in the recent years [3,9,14,[16][17][18]. Mark Weiser introduced the slicing term in [20], and presented slicing as a formalization of an abstraction technique that experienced programmers (unconsciously) use during debugging to minimize the program.…”
Section: Petri Net Reductionsmentioning
confidence: 99%
See 1 more Smart Citation